Pengaruh Profitabilitas, Likuiditas, dan Leverage terhadap Pengungkapan Corporate Social Responsibility (CSR) pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2014 - 2017 - Kristina Apriliani Putri; Elma Muncar Aditya; Nurdhiana Nurdhiana (Jurnal Ilmiah Aset, 2019)
This study aimed to find out the effect of variables such as profitability, liquidity, and leverage on Corporate Social Responsibility (CSR) Disclosure. Type of this research used was quantitative research. The total companies used in this research were 27 mining companies listed in Indonesia Stock Exchange (IDX) period 2014-2017. This research used multiple linier regression analysis. Partially Profitability (ROE) had a significant positive effect on CSR Disclosure, while Liquidity (Current Ratio) and Leverage (DER) had no effect on CSR Disclosure. The result also showed that simultaneously Profitability (ROE), Liquidity (Current Ratio) and Leverage (DER) had a significant positive effect on CSR Disclosure.